EFEKTIVITAS GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER SISWA DI SEKOLAH MENENGAH KEJURUAN NEGERI 4 KOTA JAMBI - Ellisa; Hasirah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe students' character, teachers' efforts, and the obstacles affecting the effectiveness of the Islamic Religious Education teacher in shaping students' character in class X Fashion Design 1 at State Vocational High School 4 of Jambi City, using a qualitative case-study approach with the Islamic Religious Education teacher as the key informant along with students, the principal, and the guidance and counseling teacher as additional informants. Data were collected through observation, interviews, and documentation, analyzed using the Miles and Huberman interactive model, and validated through triangulation. The results show that students' character generally developed positively, though some students remained less disciplined and responsible; the teacher shaped character through exemplary conduct, religious habituation, a personal approach, motivation, varied teaching methods, and cooperation with the school and parents; while effectiveness was still constrained by internal factors (differing student character, low motivation, limited time) and external factors (weak parental supervision, peer influence, and social media). Overall, the teacher has played an effective role in shaping students' character, though closer cooperation among the school, families, and the community is still needed. Keywords: Teacher Effectiveness, Islamic Religious Education, Students' Character, Vocational High School